Komparasi Metode Maut dan Moora dalam Pemilihan Sunscreen untuk Kulit Menggunakan Pembobotan ROC - Gusti Tarisa Mareti; Afifah Trista Ayunda (Building of Informatics, Technology and Science (BITS), 2023)
The skin is the outer layer of the human body that has various important functions. However, high sun exposure in Indonesia can cause damage to the skin due to ultraviolet rays. The use of sunscreen becomes important in preventing sunburn and skin cancer. Women with combination skin types often have difficulty choosing the right sunscreen. This study applies the Multi Attribute Utility Theory (MAUT) and Multi-Objective Optimization on The Basis of Ratio Analysis (MOORA) methods with the weighting of the Centroid Rank Order (ROC) method and the level of accuracy of MSE aims to produce decisions in choosing the right sunscreen for combination skin. At the methodology stage, data on criteria, sub-criteria, and alternatives are collected through observation and interviews. The criteria consist of 6 namely Benefit, Composition, Price, Vitamins, Side Effects, and Size. The ROC is used for weighting, while the MAUT and MOORA methods are used in the assessment and comparison of alternatives and MSE is used for the level of accuracy. The discoveries from this study hold the possibility to offer recommendations for choosing the best sunscreen for combination skin, namely A7 with the brand sunscreen Somethinc Comfort Correct for the MAUT method is 0.7134 and the MOORA method is 0.102. The results of the MSE calculation obtained a deviation value, namely the MOORA method with a value of 215.0091 better than the MAUT method of 207.4922. So that the MOORA method is the best method in choosing sunscreen for combination skin and aims to help people who are still having difficulty choosing the right sunscreen, so as to avoid mistakes in choosing inappropriate sunscreens that can have a negative impact on the skin